Health Information Technology Media by Nurses in Patient Care - Hepsibah Sharmil; Girija.J; Geetha. K (International Journal of Linguistics, Literature and Translation, 2019)
Health Information Technology (HIT) is an electronic application of patient management system in health services that yield data for enhanced patient care. This literature review article examined the ability of nurses using HIT. Nurses being the highest proportion of population in the health sector, examining the extent of HIT use from nurses, will provide a clarified outlook on the implications of HIT. Evidential literature search was done in Pubmed, Google Scholar and Science Direct and collectively it yielded 1801 articles. The articles was carefully skimmed for applicability and relevancy. The deemed inclusion criteria was met by eleven articles and it was entirely reviewed and sorted. The findings revealed that for the HIT system to be successful, from the conceptualisation of HIT, to its planning, to designing, to the application of HIT and also at the feedback stage all the members involved and affected by HIT and its implications must be consulted, especially nurses being the major number of health workers in the health care realm, its crucial that nurses are involved in every stage of HIT management and its execution. Application of HIT was found to improve skill of nurse in informatics and electronic documentation. It was found that issues like medication errors, missing-out of service by the patients were reduced. Good standard of practice was also evident  by continuation ofcare,   and   reaching the unreached  remote marginalised communities was the best of all HIT’s benefit.